Groundwater discharge tests : simulation and analysis - Clarke, David (David K.) (Developments in water science, 1988)
This book describes microcomputer programs which can be used to simulate or analyse water production well and aquifer discharge test data. Computer graphics are used to help visualise the data, and output to plotters is also catered for. Simple confined aquifers, leaky confined aquifers, unconfined aquifers and a variety of boundary conditions are dealt with. The book and the microcomputer programs it describes will allow the reader to apply very flexible computer techniques to the analysis of his well and aquifer discharge test data. The speed of the microcomputer analyses will give the user the opportunity of looking at his data in more ways than he would otherwise be able to, thus giving insights into the data that would not otherwise be possible. The simulation programs permit the production of type curve data, which can then be used in comparison with the real data, or used in becoming familiar with the operation of the analysis programs. Although primarily intended for practicing hydrogeologists and universities teaching hydrogeology, this book would also be of interest to anyone having an interest in the effects of groundwater extraction. The programs will run on IBM PCs and compatibles with colour graphics.